A Rare Case of Systemic Lupus Erythematosus with Chylous Ascites and Chylothorax - Dilek Ersil Soysal; Sezin Hizar Turan; Mustafa Ozmen; Mete Pekdiker; Mehmet Eren Kalender; Emrah Koc; Volkan Karakus (Case Reports in Rheumatology)
During the course of the disease a patient with systemic lupus erythematosus (SLE) may develop inflammation of one or more serous membranes, resulting in pleural, peritoneal, or pericardial effusion. Chylous ascites and chylothorax have rarely been described in patients with SLE. Therefore, in parallel with the analysis of blood samples, detailed analysis of the effusions should be carried out. Supportive measures are often needed to relieve the symptoms of chylothorax or chylous ascites together with the treatment of the primary disease. The available literature had reported just 4 cases of chylous ascites and/or chylothorax in association with SLE, and this patient presented here is one of the rare cases apart from the reported ones.